Treatment outcomes and recurrence rates in patients with granulomatous mastitis undergoing lumpectomy and anti-tubercular therapy - Dr. Abhinav Puri, Dr. Mahim Khan,Dr. Anil Kumar Mongia, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Granulomatous mastitis (GM) is an uncommon, persistent inflammatory breast condition that can be difficult to diagnose and treat. It often looks like breast cancer. The goal of this study was to evaluate treatment outcomes and recurrence rates in GM patients undergoing anti-tubercular therapy (ATT) after a lumpectomy. Methods: A prospective observational study was conducted on 23 female GM patients at a tertiary care center. Clinical presentations, histological findings, and treatment outcomes following lumpectomy and Category 1 ATT were investigated during a one-year follow-up. Results: The mean age of patients was 33 ± 5 years, with lump sizes ranging from 3 to 5 cm and average symptom duration of 3 months.